The Implementation Of Nahwu Learning Based On Project Based Learning At Uin Imam Bonjol Padang - Febriani, Suci; Yasmadi, Yasmadi; Indah Lestari, Sri (STAIN MAJENE, 2023)
The educational background of students is an important domain for the success of learning nahwu, so that teachers need improvement in determining the learning to be applied. The PBL strategy requires students to observe and examine practice-based assignments on the object of study being studied, so this study aims to examine the effectiveness of Project based learning (PBL)-based nahwu learning at UIN Imam Bonjol Padang and how to implement PBL in nahwu learning. The research approach used was mixed method research with a quantitative sample of 35 students from two classes while data analysis used SPSS 16 and descriptive analysis based on observation and documentation. This study shows that learning nahwu using the PBL design is effective for students' cognitive understanding by calculating the t-test is greater than the t-table, while the implementation of PBL is based on needs analysis and practice searching for examples of sentences in the Qur'an. This study corroborates that learning nahwu using project based learning is able to increase cognitive understanding based on inductive techniques in tracing verses of the Qur'an. This study recommends further research to analyze nahwu learning strategies that are more varied with various samples and methods.